THE INFLUENCE OF MANAGERIAL LEADERSHIP STYLE AND TEACHER PERFORMANCE ON THE QUALITY OF EDUCATION MEDIATED INNOVATIVE TEACHERS AT MTS AL-ISHLAH - Aurelius Redi; Eko Santoso; Riky Sugianto; Retno Purwani Setyaningrum (SEAN Institute, 2023)
The managerial leadership style of the madrasa principal in his capacity as a leader and teacher as an educator is very important for the success of the quality of education. This research is a descriptive qualitative research. This type of research is qualitative with the participation of teachers at Madrasah Tsanawiyah Al-Ishlah. This research analyzes the data using the method of collecting data through documentation, interviews and direct observation in the field using case studies. The results of the study explain data collection, data reduction, data display, and data inference. Data collection instruments by way of in-depth interviews, observation, and documentation. This study found that some teachers had used managerial leadership styles but other practical activities had not been carried out optimally. This is because the support from teacher performance and teacher innovation has not been optimal, so that the quality of education has not been fully achieved. Even so, teachers realize that managerial leadership style and teacher performance with innovative mediation can improve teacher quality.